2015
DOI: 10.1007/s11230-015-9577-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for the existence of species complexes within Macvicaria Gibson & Bray, 1982 (Digenea: Opecoelidae) in the western Mediterranean, with descriptions of two new species

Abstract: Morphological and molecular characterisation of specimens of Macvicaria spp. (Digenea: Opecoelidae) from five species of Mediterranean sparids (Teleostei: Sparidae) sampled in the Bizerte Lagoon and the Bay of Bizerte (Tunisia) revealed the presence of two species complexes designated as ''obovata'' and ''crassigula'' groups. Detailed comparative morphological and phylogenetic analyses revealed that two of the specimen sets, one from each complex, represent species new to science. M. maamouriae n. sp. from Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition, little effort has been made, hitherto, to explore the genetic validity of Atlantic species. Relatively recent works by, for example, Jousson (Jousson et al, 1999 , 2000 ; Jousson, 2001 ), Blasco-Costa (Blasco-Costa et al, 2009a , b , 2010 ), Antar (Antar et al, 2015 ) in the Mediterranean and Curran, Pulis and Andres (Andres et al, 2014 ; Curran & Pulis, 2014 ; Pulis et al, 2014 ) in the Gulf of Mexico, are the exception. In the wider Atlantic the study of some deep-sea species of Lepidapedon Stafford, 1904 and other lepidapedids and fellodistomids (Lumb et al, 1993 ; Bray et al, 1994 , 1999 ) has shown that cryptic species are common.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, little effort has been made, hitherto, to explore the genetic validity of Atlantic species. Relatively recent works by, for example, Jousson (Jousson et al, 1999 , 2000 ; Jousson, 2001 ), Blasco-Costa (Blasco-Costa et al, 2009a , b , 2010 ), Antar (Antar et al, 2015 ) in the Mediterranean and Curran, Pulis and Andres (Andres et al, 2014 ; Curran & Pulis, 2014 ; Pulis et al, 2014 ) in the Gulf of Mexico, are the exception. In the wider Atlantic the study of some deep-sea species of Lepidapedon Stafford, 1904 and other lepidapedids and fellodistomids (Lumb et al, 1993 ; Bray et al, 1994 , 1999 ) has shown that cryptic species are common.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, two were recognised using both morphological and molecular methods (see Antar et al, 2015). In addition, the life cycle of Proctoeces maculatus (Looss, 1901) was studied in Bizerte Lagoon using the same methods, resulting in our suggesting the existence of cryptic species based on the different developmental stages of the life-cycle of this ‘species’ (Antar & Gargouri, 2015). In the present work, we provide information on the diversity of digenean species in teleost fishes off the northern coast of Tunisia (Bay of Bizerte) and compare our results with those already published for the other localities of the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…The digenean fauna of sparid fish has been the subject of various studies in the Mediterranean Sea, among them we will cite the works of: Bartoli, 1987aBartoli, , 1987bBartoli & Gibson, 1989;Bartoli et al, 1989aBartoli et al, , 1989bSaad-Fares & Maillard, 1990;Sasal et al, 1999;Kostadinova & Gibson, 2009;Sanchez et al, 2013Sanchez et al, , 2014. Moreover, we can also mention recent works undertaken on the parasitofauna of sparidae fishes in the Mediterranean Sea, including the work of Merzoug et al, 2012;Abid Kachour et al, 2013;Antar & Gargouri Ben Abdallah, 2013;Abid Kachour, 2014;Antar et al, 2015;Bellal et al, 2016. However, this contribution is still incomplete, knowing that sparidae are considered as ideal host fish for the larval and adult stages. The biodiverty of the community of the digenean parasites within each host will allow us to highlight their trophic Digenean parasites in two sparid fishes congeneric and of commercial importance from Algeria TISTICA software (Statsoft statistica version 12.5.192.7).…”
Section: Methodsmentioning
confidence: 92%